Management of child victims of acute sexual assault: Surgical repair and beyond - Sham, Minakshi (Medknow Publications & Media Pvt Ltd, 2013)
AIM: To evaluate the outcome of definitive repair of anogenital injuries (AGI) in child victims of acute sexual assault. SETTINGS AND DESIGN: It is a prospective study of emergency care provided to child victims of acute sexual assault at a tertiary care Pediatric Surgical Unit in Maharashtra, India. MATERIAL AND METHODS: Out of 25 children, who presented during January 2009-December 2010 with suspected sexual assault, five children (one male and four female, between 4-9 years of age), had incurred major AGI. These children underwent definitive repair and a diverting colostomy. Perineal pull-through was performed in the male child with major avulsion of rectum. One 4-year-old girl with intraperitoneal vaginal injury required exploratory laparotomy in addition. RESULTS: The postoperative period and follow-up was uneventful in all our patients. Four out of five patients have excellent cosmetic and functional outcome with a follow-up of 2-4 years. Our continence results are 100%. CONCLUSION: Children with acute sexual assault need emergency care. To optimally restore the distorted anatomy, all major AGI in such children should be primarily repaired by an expert, conversant with a child’s local genital and perineal anatomy. Along with provision of comprehensive and compassionate medical care, prevention of secondary injuries should be the ultimate goal.